Analysis of a Circular Water Tank Considering Lateral Load Using Analysis Tool - Kusum; Pradeep Nirmal; Pratik Kathale (International Journal of Scientific Research in Civil Engineering, 2025)
Circular water tanks are widely used in water distribution systems due to their efficient design and cost-effectiveness for storing moderate water volumes. However, ensuring their structural integrity under water pressure and external loads is crucial. This research utilizes STAAD Pro, a popular structural analysis and design software, to model and analyze a circular water tank, evaluating its response to various loading conditions.
Keywords: Circular Water Tank; hydrostatic pressure; seismic analysis; Staad Pro